Alternative Recommendation For Fingerprint Registration Policies And Waiting Times On Revisit Compliance Of Schizophrenia Patients At Tangerang City Hospital - Masithoh, Dewi; Fauziah, Munaya; Purnamawati, Dewi (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Background: The fingerprint registration system has been implemented at Tangerang City Hospital since 2024 for all clinics as an effort to digitize outpatient services. However, the implementation of this system for patients with mental disorders such as schizophrenia has created access barriers, such as anxiety, ignorance, and emotional resistance. Long waiting times also hinder patient compliance with follow-up visits. Objective: This study aims to explore the experiences of schizophrenia patients and their family caregivers regarding the fingerprint registration system, waiting times, and interactions with healthcare professionals. This study also develops policy recommendations based on the experiences of service users. Methods: This qualitative study used a phenomenological approach using in-depth interviews with 20 informants (family members, healthcare professionals, registration coordinators, the Head of Medical Records and the Head of the Yanmed Work Team), as well as non-participatory observation and focus group discussions (FGDs). Analysis was conducted based on content. Results: Patients with schizophrenia experienced emotional, technical, and psychological barriers in the fingerprinting process. This non-inclusive system caused stress and discomfort, resulting in low compliance with follow-up visits. Waiting times exceeding two hours also worsened patients' psychological well-being. Most informants suggested a dedicated pathway and standard operating procedures (SOPs) for mental-friendly services as alternative policies. Conclusion: The fingerprint-based outpatient service policy is not yet inclusive of vulnerable groups such as schizophrenia patients. Reformulation of SOPs and policies for mental-friendly services based on empathy, efficient service duration, and alternative identity verification methods is needed.